(untitled) (Quinto Sol, 2016)
This paper aims at increasing the knowledge related with specialized historiography on the field of migration and tuberculosis in the early decadesof the twentieth century, within the context of the internal migration that arrived to the province and the city of Córdoba. Technical literature and testimonies of the time are used as sources. The article is organized in two main sections. On the one hand, it analyses the type of migration that arrived to the city in the context of a healthcare system regarding tuberculosis’ treatment under construction. On the other, it analyses the discourses and concepts that emerged from local power sectors in a scenario characterized by low-income immigrants and a weak healthcare system regarding tuberculosis’ treatment. The paper identifies the existence of concepts and discourses that tended to make the immigrant responsible for spreading the diseases to "healthy" residents and "invading" the city of Cordoba with sick people as well as to bring the collapse of the healthcare system.